MANAJEMEN KOMUNIKASI PARIWISATA DINAS KEBUDAYAAN DAN PARIWISATA PROPINSI SULAWESI SELATAN (Studi Manajemen Komunikasi Program Pariwisata Lovely December Tahun 2010 di Kabupaten Tana Toraja dan tahun 2011 di Kabupaten Toraja Utara) - , RIZQY ALFIYATY; , Dr. Phil. Hermin Indah Wahyuni, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aimed to find out: Lovely December communication management program internally and externally. The study was conducted using qualitative methods using a case study approach. This approach is expected to explain the findings in the field more detailed, in-depth, and thorough. The research uses a conceptual framework of communication management, stakeholders, promotion of tourism (conventional) and internet opportunities and use of new media to analyze the findings in the field. The results showed that: (first) at the planning stage to determine the communicator as the party responsible for the delivery of messages / information, the type of information / messages to be conveyed through the selection of communication media has been adapted to target communications (communicant) in the hope of reaching the target program tourism